Fairness in Taxation : Exploring the Principles - Panitch, Leo; Cassin, A. Marguerite; Green, Leslie; Osberg, Lars, 1946-; Head, John G. (Book collections on Project MUSE., 1993)
The papers in this volume explore the idea of distributive justice and fairness in taxation. The collection begins with Head's excellent presentation and analysis of equity in the public finance literature. The other authors, starting from this point, critique and amplify the concept from various philosophical perspectives and academic disciplines.